2000
DOI: 10.1067/mva.2000.106488
|View full text |Cite
|
Sign up to set email alerts
|

Arm vein conduit is superior to composite prosthetic-autogenous grafts in lower extremity revascularization

Abstract: In this study, multisegment autogenous arm vein was used successfully in a wide variety of lower extremity revascularization procedures and achieved good long-term patency and limb salvage rates, well in excess of those achieved with composite prosthetic-autogenous grafts. The use of autogenous conduit appears to offer superior results to composite conduit in lower extremity revascularization. The superior durability of arm vein makes it one of the alternative conduits of choice when an adequate greater saphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 36 publications
0
34
0
1
Order By: Relevance
“…Of these, about 200.000 are small and medium diameter grafts (4-6mm) for vascular access and to relieve lower limb ischemia and more than 600.000 are small diameter grafts (1-4mm) needed for coronary bypass procedures. The conduit of choice for small diameter vascular graft surgery is the autologous vein or artery, but these are not available in 25-30% of patients due to preexisting conditions or previous harvesting [1]. Current grafts are made of polyethylene terephtalate (Dacron) or expanded polytetrafluoroethylene (ePTFE), or biologically derived conduits such as cryopreserved saphenous vein allografts and decellularized bovine ureters [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, about 200.000 are small and medium diameter grafts (4-6mm) for vascular access and to relieve lower limb ischemia and more than 600.000 are small diameter grafts (1-4mm) needed for coronary bypass procedures. The conduit of choice for small diameter vascular graft surgery is the autologous vein or artery, but these are not available in 25-30% of patients due to preexisting conditions or previous harvesting [1]. Current grafts are made of polyethylene terephtalate (Dacron) or expanded polytetrafluoroethylene (ePTFE), or biologically derived conduits such as cryopreserved saphenous vein allografts and decellularized bovine ureters [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that LEAB using arm vein conduits showed 3-year graft patency and limb salvage rates ranging from 40% to 73% and 63% to 92%, respectively [8,12,13,16]. In our series, the overall 3-year patency and limb salvage rates were 60.9% and 94.4%, respectively.…”
Section: Discussionmentioning
confidence: 44%
“…Previous studies showed that results from infrapopliteal bypass using prosthetic graft have been less satisfactory than those obtained with arm vein (Table 4) [8,12,16,1925]. In our institute, we prefer arm vein graft as a first choice of alternative graft in infrapopliteal bypass in the absence of adequate saphenous vein.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Second, only an autogenous vein of good quality with a large diameter must be used. Prior studies have reported unfavorable outcomes of composite prosthetic-autogenous grafts [11,23,24]; however, these studies have a possibility of selection bias, and the details of the procedures using composite grafts were not well described. Third, the operation must be performed in a planned manner.…”
Section: Discussionmentioning
confidence: 99%